The effect of the Shorter Stays in Emergency Departments health target on the quality of ED discharge summaries. Issue 12 (11th May 2016) - Harper, Alana; Jones, Peter; Wimsett, Jordon; Stewart, Joanna; Le Fevre, James; Wells, Susan; Curtis, Elana; Reid, Papaarangi; Ameratunga, Shanthi
Abstract : Objective: Time targets for ED stays are used as a policy instrument to reduce ED crowding. There is debate whether such policies are helpful or harmful, as focus on a process target may divert attention from clinical care. The objective of this study is to investigate whether the Shorter Stays in Emergency Departments target in New Zealand was associated with a change in the quality of ED discharge information provided to primary care providers. Methods: The quality of discharge summaries was assessed retrospectively over time using chart review. Logistic regression was used to account for secular trends with adequate or not as the dependent variable. Explanatory variables were: age, ethnicity, deprivation, triage category, year, the step at target introduction (2009) and the change in slope before and after the target. Results: Of 500 randomly selected discharge summaries, 491 (98.2%) were included in the analysis. There was evidence of a decrease over time in the proportion of adequate discharge summaries before the introduction of the target (slope estimate (SE) −0.43 (0.20), p=0.02). A step at the target introduction could not be shown (p=0.47). There was evidence of an improvement over time from pre-target to post-target: slope afterwards 0.33, estimate of change in slope (SE) 0.76 (0.27), p=0.006. Conclusions: There was no reduction in the quality of discharge summaries following the introduction of the shorter stays in ED target and trends in quality improved. These findings deserve replication in other hospitals which may experience different challenges.